Isolasi Bakteri Rhizosfer Penghasil Antimikroba Pada Akar Tanaman Jeruk Nipis (Citrus aurantifolia Swingle) - rusman hasanuddin (Sasambo Journal of Pharmacy, 2020)
Isolation of rhizosphere bacteria producing antimicrobial soil around the roots of the lime plant (Citrus aurantifolia Swingle). This study aims to obtain rhizosphere bacterial isolates originating from the soil around the roots of the Lime Plant (citrus aurantifolia Swingle) which can be used as antimicrobials. The research method was taken from the soil around the roots of the Lime plant and then diluted with dilutions of 10-1, 10-2, 10-3 to 10-5 dilution, then poured on NA media containing test microbes. The resulting isolates were then purified and coded JS-1, JS-2, JS-3. Microscopic examination results added 2 gram-negative bacterial isolates namely JS-1 and JS-3, while 1 gram-positive bacterial isolate was JS-2. The resulting isolate was then fermented with NB medium which produced supernatant and biomass, the supernatant was tested antimicrobial which produced active compounds of rhizosphere bacteria (JS-1 and JS-3) from the root soil of the Lime plant have the ability as an antimicrobial activity against Staphylococcus aureus, Escherichia Candida albicans coli and fungal test